Utilization of insecticide-treated bed nets and associated factors among households in Pawie District, Benshangul Gumuz, Northwest Ethiopia - Tilahun Merga; Mesafint Molla Adane; Tebkew Shibabaw; Fekie Ahemed Salah; Lemessa Jira Ejigu; Sileshi Mulatu (Scientific Reports)
Abstract Introduction: Insecticide-treated bed nets are often used as a physical barrier to prevent infection of malaria. In Sub-Saharan Africa, one of the most important ways of reducing the malaria burden is the utilization of insecticide-treated bed nets. However, there is no sufficient information on the utilization of insecticide-treated bed nets and their associated factors in Ethiopia. Objectives: This study aimed to assess the utilization of insecticide-treated bed nets and associated factors among households in Pawie District, Benshangul Gumuz, North West Ethiopia. Methods: A community-based cross-sectional study was conducted in the Pawie district to identify factors influencing the use of insecticide-treated nets (ITNs). Diverse household groups were engaged, and data were collected using a structured questionnaire and observational checklists by trained interviewers. The data were entered into Epi-Data version 3.1 and analyzed using SPSS version 23. Advanced statistical methods, including binary and multi-variable logistic regression, were employed to examine the factors associated with ITN utilization. Results: From the total of 633 respondents, more than two third, 438 (69.2% with 95% CI: 65.2%, 72.5%) had utilized insecticide-treated bed nets during the early morning of the interview. Approximately 297 respondents (67.8%) successfully hung their insecticide-treated nets (ITNs) properly during the early morning of observation. In this study, 406 respondents (64.1%, 95% CI: 60.5, 68.1) showed a solid understanding of insecticide-treated nets (ITNs) utilization. Key predictors for the utilization of insecticide-treated bed nets (ITNs) included age (AOR = 1.86, 95% CI: 1.11, 3.13, p = 0.019), educational status (AOR = 0.45, 95% CI: 0.26, 0.77, p = 0.008), knowledge level (AOR = 2.64, 95% CI: 1.89, 3.81, p < 0.001), and family size (AOR = 1.89, 95% CI: 1.31, 2.74, p = 0.001). All of these variables were found to be statistically significant for the utilization of insecticide-treated bed net. Conclusions: Utilization of the insecticide-treated bed nets (ITNs) remains low in the study area. To address this, it is crucial to raise public awareness and improve utilization of the insecticide-treated bed nets (ITNs) to decrease malaria transmission in the district. Ongoing health education initiatives, including demonstrations on the proper way to hang bed nets, will be essential in fostering better practices and improving community health outcomes.